Long-term Storage of Bacterial Isolates by Using Tryptic Soy Broth with 15% Glycerol in The Deep Freezer (-70 to -80 °C). Issue 1 (November 2021) - Sunarno,; Nursofiah, S; Hartoyo, Y; Amalia, N; Febrianti, T; Febriyana, D; Saraswati, R D; Puspandari, N; Sariadji, K; Khariri,; Rukminiati, Y; Muna, F; et al.
Abstract: For different bacterial preservation techniques, there is no single method applicable for all bacteria. This study aimed to assess the viability of seven species/species groups of clinical bacteria isolates on the long-term storage (more than 5 years) by using Tryptic Soy Broth with 15% glycerol in the deep freezer (-70 to -80°C). A total 10, 654 clinical bacteria isolates used as samples in this study. The isolates consisted of seven species/species groups (i.e. Escherichia coli, Campylobacter spp, Shigella spp, Vibrio spp, Salmonella spp, Aeromonas hydrophila, and Neisseria gonorhoeae). The isolates were collected from some previous studies and preserved in the Tryptic Soy Broth (TSB) with 15% glycerol and stored in the deep freezer (-70 to -80°C) for more than five years. The samples were revived on the suitable medium to evaluate the viability of bacteria. Identification conducted by microscopic examination, biochemical test, and latex agglutination. The study showed that the viability of Salmonella spp, Shigella spp, Aeromonas hydrophila and E. coli was 100%, while Campylobacter spp, Vibrio spp, and N. gonorhoeae were 66.7%, 66.4%, and 52.5% respectively. We concluded that viability of Salmonella spp, Shigella spp, A. hydrophila, and E. coli was optimum thus better than Campylobacter spp, Vibrio spp, and N. gonorhoeae for more than 5 years storage by using TSB with 15% glycerol in the deep freezer (-70 to -80 °C).